Crystalline‐Water/Coordination Induced Formation of 3D Highly Porous Heteroatom‐Doped Ultrathin Carbon Nanosheet Networks for Oxygen Reduction Reaction. Issue 20 (24th August 2018) - Liu, Tingting; Feng, Shi; Huo, Jia; Li, Qiling; Xie, Chao; Wang, Shuangyin
Abstract: Development of highly efficient electrocatalysts with low cost for oxygen reduction reaction (ORR) is crucial for their application in fuel cells and metal‐air batteries. In this work, we report a synthesis of 3D heteroatom‐doped ultrathin carbon nanosheet networks directly starting from solid raw materials. This method represents an operationally simple, general, and sustainable strategy to various ultrathin carbon nanosheet networks. Evaporation of crystalline water and coordination interaction are proposed to be responsible for the formation of the 3D carbon nanosheet networks. The carbon nanosheet networks possess high surface area with micro‐ and macropores, large pore volume, ultrathin nanosheet structure, and effective N/S‐co‐doping. The as‐prepared materials show outstanding electrocatalytic ORR performance with more positive onset potential and half‐wave potential, good methanol tolerance, and excellent stability, compared with those of the porous carbons derived from the ZIF counterpart and commercial Pt/C. This work not only provides highly active ORR electrocatalysts via an operationally simple and green process and also demonstrates a general method to prepare 3D ultrathin carbon nanosheet networks without any additional template and solvent. Abstract : Operationally simple : 3D highly porous heteroatom‐doped ultrathin carbon nanosheet networks have been synthesized directly starting from solid raw materials without any additional template. The ultrathin structure, hierarchical porosity, and heteroatom‐doping endow as‐prepared ultrathin carbon nanosheet networks with outstanding eletrocatalytic ORR performance.